2023
DOI: 10.1172/jci.insight.170681
|View full text |Cite
|
Sign up to set email alerts
|

Combined anti-S1 and anti-S2 antibodies from hybrid immunity elicit potent cross-variant ADCC against SARS-CoV-2

Abstract: Antibodies capable of neutralizing SARS-CoV-2 are well studied, but Fc receptor–dependent antibody activities that can also significantly impact the course of infection have not been studied in such depth. Since most SARS-CoV-2 vaccines induce only anti-spike antibodies, here we investigated spike-specific antibody-dependent cellular cytotoxicity (ADCC). Vaccination produced antibodies that weakly induced ADCC; however, antibodies from individuals who were infected prior to vaccination (hybrid immunity) elicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…Taken together, these results support the established ( 20 , 43 , 44 ) idea that pre-exposure to SARS-CoV-2 Ags, whether by natural infection or heterologous vaccination (e.g., Janssen or AstraZeneca), confers a more rapid and robust response to the mRNA primary vaccine series with the following adaptive immunological features: 1) increased circulating anti-RBD Abs ( Fig. 1A, 1D ); 2) increased frequency of anti-RBD IgG-producing B cells ( Fig.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Taken together, these results support the established ( 20 , 43 , 44 ) idea that pre-exposure to SARS-CoV-2 Ags, whether by natural infection or heterologous vaccination (e.g., Janssen or AstraZeneca), confers a more rapid and robust response to the mRNA primary vaccine series with the following adaptive immunological features: 1) increased circulating anti-RBD Abs ( Fig. 1A, 1D ); 2) increased frequency of anti-RBD IgG-producing B cells ( Fig.…”
Section: Resultssupporting
confidence: 90%
“…To assess the dynamic range of humoral response to vaccination, we also compared matched subject anti-RBD responses across time ranges and found that pre-exposed subjects demonstrated a significantly higher differential response over the prevaccination to the 4- to 11-wk interval ( Fig. 1B , gMFI: unexposed 5.11e4, pre-exposed 10.1e4, p = 0.033), consistent with the observation that pre-exposure confers the capacity to mount a more dynamic increase in anti-RBD IgG upon subsequent vaccination ( 20 , 43 , 44 ). Supporting the specificity of our Ab response measurement platform, Ab levels to related endemic coronavirus variants (OC43 and HKU) did not change in response to SARS-CoV-2 vaccination ( Supplemental Fig.…”
Section: Resultssupporting
confidence: 80%
“…In addition, the antibody-mediated Fc effector functions such as antibody dependent cellular cytotoxicity (ADCC) are important components of immunological protection. 87 , 88 , 89 Unfortunately, ADCC activity was not detected withe the current IgG-scFv bispecific antibodies Bis-Beb ( Figure S7 ). Furthermore, there are concerns regarding in vivo efficacy of the IgG-scFv formatted bispecific antibody.…”
Section: Discussionmentioning
confidence: 97%
“…Working plasma dilutions for assessing IgG and IgA antibody levels were 1:100 and 1:50, respectively, and conjugate dilutions were 1:50,000 for anti-IgG*HRP and 1:25,000 for anti-IgA*HRP. Variability and reproducibility of this assay format have been described [ 12 , 15 , 17 ]. All between-group comparisons shown were run in the same assay.…”
Section: Methodsmentioning
confidence: 99%
“…While it is mucosal IgA that is most likely to contribute protection from respiratory infections, for ease and simplicity, vaccine-induced Ab production studies primarily focus on the capacity of circulating IgG to neutralize SARS-CoV-2 variants [ 7 , 8 , 9 , 10 , 11 ]. Vaccine-induced anti-SARS-CoV-2 IgG responses are optimized with sufficient time intervals between doses, yet fall short of responses seen with hybrid immunity [ 12 , 13 , 14 , 15 ]. Furthermore, subjects who experience an infection with SARS-CoV-2 variants following vaccination with ancestral-S-based vaccines continue to display preferential IgG responses against ancestral S. This favouring of an immune response toward previously encountered, closely related versions of an extant antigen is known as original antigenic sin or immune imprinting [ 16 ].…”
Section: Introductionmentioning
confidence: 99%